FAST FOOD CONSUMPTION AND OBESITY STATUS ON ELEMENTARY SCHOOL IN SD NEGERI 03 PENATIH DAN SD NEGERI 17 DANGIN PURI IN DENPASAR CITY - Ni gusti ayu Putu Santia riadipa (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
The prevalence of obesity in children aged 5-12 years has increased from (9.2%) 2010 to (18.8%) in 2013, the city of Denpasar prevalence of obesity 11,9% 2011. The research objectives know the description of fast food consumption and obesity status elementary school. The study was conducted at SDN 03 Penatih and SDN 17 Dangin Puri in May 2018. Type of Observational research with cross sectional research design. The design of interview data on fast food consumption and nutritional status measurement. The data were obtained in two different schools of study of fast food consumption of fried chicken 78 samples (100.0%), hamburger 28 samples (73.6%) and 22 samples (55.0%), 36 samples (94.7%) and 33 samples (82.5 %), instant noodles 38 samples (100.0%) and 36 samples (90.0%), 38 sample nugget (100.0%) and 38 samples (95.0%), sausage 32 samples (84.2%) and 32 samples (80.0%). Frequency of fried chicken 22 samples (57.9%) daily 1-2 times and 20 samples (50%) daily 1-2 times, 15 samples (39.5%) weekly 1-2 times and 20 samples (50%) weekly 1-2 times , 1 sample (2.6%) weekly 3 times. Average Energy contribution 625.16 and 716.30 kcal, fat 44.46 and 50.37 grams, carbohydrates 50.74 and 57.25 grams. Average Nutritional Status and Contribution of obesity nutritional status 8 energy samples 666.9 and 1056.6 kcal, fat 44.8 and 68.2 grams, carbohydrates 59.3 and 91.4 grams. There are still nutritional problems in both primary schools, parents are advised to pay attention and keep the consumption of elementary school so as not to over-eat fast food. For other researchers can be used as basic data for further research related to the consumption of fast food of elementary school.Keywords: Fast food, Obesity Status